PECULIARITIES OF DIAGNOSTICS, SURGICAL TACTICS AND RESTORATION OPERATIONS IN NECROTIZING INFECTION OF SOFT TISSUES - M.KH. NABIEV; SH. YUSUPOVA; A.T. AZIMOV; Т.B. BORONOV (Avicenna Tajik State Medical University, 2018)
Objective: Improving diagnostic results and surgical treatment of necrotizing soft tissue infection. Methods: Analyzed the results of diagnostics and treatment of 68 patients with various forms of necrotizing infection for the period 2010-2017. There were 32 men (53.8%), women - 36 (46.2%) at the age of 30-84. In 27 (39.7%) patients the necrotic form of erysipelas occurred, in 41 (60.3%) necrotizing fasciitis and myonecrosis. In 60.3% of cases, the pathological process was localized in the region of the lower extremities. More than 90% of the patients had concomitant diseases, among them diabetes mellitus (78.2%), arterial hypertension (83.3%), coronary artery disease (75.6%) and anaemia of varying severity (74.3%). Results: The clinical picture of streptococcal necrotizing fasciitis (n=31) and myonecrosis (n=10) in the early stages was characterized by the absence of pathognomonic symptoms. The discrepancy between the severity of the general condition and local status in a number of cases led to the belated surgical intervention and, as a result, extensive postoperative wounds, requiring 16 cases of plastic closure. In 12 (75%) cases, full engraftment was noted, in 3 (18.7%) partial engraftment and in 1 (6.3%) observation - complete necrosis of the graft. Conditions of transplant engraftment were corrected carbohydrate metabolism, preserved regional hemodynamics and the presence of actively granulating wound surface. Conclusion: Necrotizing infection, which is a nonspecific inflammatory process of soft tissues, is characterized by progressive necrosis, rapid spreading, difficulty in diagnosing in the early stages of the disease, pronounced intoxication and high lethality.